Imbalanced transfer of trade-related air pollution mortality in China. (18th August 2020) - Zhao, Hongyan; Liu, Yang; Geng, Guannan; Li, Xin; He, Wenjie; Chen, Xiaoting; He, Kebin; Zhang, Qiang
Abstract: Revealing the determinants and associated impacts of the transboundary pollution caused by trade is a critical issue when promoting the joint control among regions. This interdisciplinary study utilizes physical, economic and epidemiological methods to explore the anthropogenic PM2.5 related mortality driven by interprovincial trade within China and its determinants. The results showed that 68% of the mortality flow in China was from the central and north plain area, with 29% occurring within these regions and 39% flowing to other eastern and western provinces. The high death intensity resulting from higher exports of heavily polluted agricultural and heavy industry products dominated the trade surplus of PM2.5 mortality for the central and northern plains of China; these bring an imbalanced economic return for these regions, with only 43% of the value added generated in interprovincial trade being retained in these regions. Our study provides a more comprehensive picture of how atmospheric pollution deaths were caused by domestic trade within China, which may facilitate the multilateral pollution mitigation actions from an environmentally economic balanced perspective.